Defining investment additionality for CDM projects: Practical approaches - Thomas Langrock; Axel Michaelowa; Sandra Greiner (Hamburg Institute of International Economics (HWWA), 2000)
The environmental integrity of the CDM under the Kyoto Protocol depends on the possibility to avoid giving emission credits to projects that would have happened anyway. Whether and how ?Investment Additionality? of CDM projects has to be determined is currently part of climate negotiations. We discuss the rationale of companies to invest in projects and analyse possible criteria to determine Investment Additionality from a theoretical point of view. A number of case studies is used to show the implications of the different criteria. The use of a single criterion is not possible, especially due to the importance of non-monetary barriers. However, some criteria are better than others. Moreover, the institutional framework for the selection and application of criteria is very important. Concluding, we suggest a combination of a threshold Internal Rate of Return with a risk factor as primary criterion. To take nonmonetary barriers into account, additional criteria could be used such as the existence of similar privately financed projects in the host country. If no explicit criterion is politically feasible, stringent baseline methodologies could at least capture some aspects of Investment Additionality. – – Die umweltpolitische Integrität des im Kyoto-Protokoll verankerten CDM hängt davon ab, ob Projekte, die ohnehin stattgefunden hätten, Emissionsgutschriften erhalten können. Ob und wie die ?Zusätzlichkeit der Investition? nachgewiesen werden muss, ist derzeit Bestandteil der Klimaverhandlungen. Wir diskutieren die Entscheidungsgründe, die Firmen zu Investitionen in Projekte bewegen und analysieren mögliche Kriterien für die Bestimmung der Zusätzlichkeit aus einer theoretischen Perspektive. Darüber hinaus werden Fallstudien zur Untersuchung der Auswirkungen der verschiedenen Kriterien herangezogen. Sie zeigen, dass die generelle Beschränkung auf ein einzelnes Kriterium nicht möglich ist. Jedoch sind einige Kriterien besser als andere. Außerdem sind die institutionellen Rahmenbedingungen für die Auswahl und Anwendung der Kriterien sehr wichtig. Zusammenfassend befürworten wir die Kombination eines Schwellenwerts für die interne Ertragsrate mit einem Risikofaktor. Um nicht-monetäre Hindernisse zu berücksichtigen, können zusätzliche Kriterien wie die Existenz von ähnlichen, privat finanzierten Projekten im Gastland überprüft werden. Wenn kein derartiges Kriterium politisch durchsetzbar ist, können strenge Regeln für die Referenzfallbestimmung zumindest einige Aspekte der Zusätzlichkeit einfangen.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Umweltschutzinvestition; Projektbewertung; Internationaler Transfer; Welt